2018
DOI: 10.1371/journal.pone.0206134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet protein restriction on progression of chronic kidney disease: A systematic review and meta-analysis

Abstract: BackgroundDietary protein restriction has long been thought to play an important role in the progression of chronic kidney disease (CKD); however, the effect of dietary protein on the rate of decline in kidney function remains controversial.ObjectiveWe undertook a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the influence of protein restriction on chronic kidney disease.MethodOvid MEDLINE (from 1946 to March 5, 2016), EMBASE (from 1966 to March 5, 2016), and the Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 61 publications
2
54
0
4
Order By: Relevance
“…A low-protein diet (LPD) has been found to delay chronic kidney disease (CKD) progression in studies on animal and carefully selected patients with CKD [1][2][3][4]. In the systematic review and meta-analysis of randomized controlled trials, a protein-restricted diet may reduce kidney function deterioration rate and renal failure risk of patients with CKD, but did not produce a positive effect on all-cause death events [5]. However, considering non-diabetic patients with CKD 4 and 5, a recent systematic review and meta-analysis of randomized controlled trials showed that compared with a normal-protein diet, an LPD may make little difference in the rate of decreasing renal function in non-diabetic patients with CKD 4 and 5 who progress to renal replacement therapy, but a very low protein diet (VLPD) probably decrease the number of non-diabetic patients with CKD 4 and 5, who progress to renal replacement therapy [6].…”
Section: Introductionmentioning
confidence: 99%
“…A low-protein diet (LPD) has been found to delay chronic kidney disease (CKD) progression in studies on animal and carefully selected patients with CKD [1][2][3][4]. In the systematic review and meta-analysis of randomized controlled trials, a protein-restricted diet may reduce kidney function deterioration rate and renal failure risk of patients with CKD, but did not produce a positive effect on all-cause death events [5]. However, considering non-diabetic patients with CKD 4 and 5, a recent systematic review and meta-analysis of randomized controlled trials showed that compared with a normal-protein diet, an LPD may make little difference in the rate of decreasing renal function in non-diabetic patients with CKD 4 and 5 who progress to renal replacement therapy, but a very low protein diet (VLPD) probably decrease the number of non-diabetic patients with CKD 4 and 5, who progress to renal replacement therapy [6].…”
Section: Introductionmentioning
confidence: 99%
“…2 The role of dietary protein restriction in slowing progression of CKD is more controversial, although several meta-analyses indicate a beneficial, albeit small effect. 3,4 In autosomal dominant polycystic kidney disease (ADPKD) specifically, there are only scarce data on the renal effects of salt and protein intake.…”
mentioning
confidence: 99%
“…In a randomised trial 22 conducted in patients who had an eGFR less than 30 mL/min/1.73 m 2 , a ketoanalogue‐supplemented vegetarian diet with protein intake of 0.3 g/kg/day was associated with a prolonged dialysis‐free survival, compared with a protein intake of 0.6 g/kg/day. However, in a meta‐analysis 19 of 19 trials with 2492 subjects who had either a low eGFR or albuminuria, a low‐protein diet reduced the risk of ESRD (odds ratio 0.64, 95% CI 0.43‐0.96), but did not lower all‐cause mortality (odds ratio 1.17, 95% CI 0.67‐2.06). In another meta‐analysis 28 that included 17 studies with a total of 2996 subjects who had stages 3‐5 CKD, a protein intake of 0.5‐0.6 g/kg/day was not significantly associated with a lower risk of mortality (risk ratios 0.77, 95% CI 0.51‐1.18), compared with a protein intake of ≥0.8 g/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomised trial 22 conducted in 207 patients with an estimated glomerular filtration rate (eGFR) less than 30 mL/min/1.73 m 2 , the authors reported that a ketoanalogue‐supplemented vegetarian diet with a protein intake of 0.3 g/kg/day led to a prolonged dialysis‐free survival, compared with a protein intake of 0.6 g/kg/day. Nevertheless, mortality risk was not reduced with a low‐protein diet (odds ratio 1.17, 95% CI 0.67‐2.06) in meta‐analysis 19 of 19 trials with 2492 subjects who had either a low eGFR or albuminuria. In contrast, a protein intake of 0.28 g/kg/day appeared to increase mortality risk (hazard ratios, HRs 1.92, 95% CI 1.15‐3.20) 23 compared with a protein intake of 0.58 g/kg/day in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation